Pengaruh Halal Green Packaging, Green Halal Product, Halal Green Perceived Value Terhadap Green Purchase Intention - Samsul Arifin (ITB AAS INDONESIA Surakarta, 2022)
The issue of the environment is now a problem that is most often discussed by the wider community. The problem of air pollution, water pollution, and the most phenomenal problem is the waste problem. Based on statistical data, the second rank of domestic waste producer in Indonesia, namely the production of plastic waste of 5.4 million tons per year, companies that implement green marketing is now a business focus for many companies. This study aims to obtain empirical evidence that the Halal Green Packaging, Green Halal Product, Halal Green Perceived Value variables collectively affect green purchase intention on Ades bottled water in Jepara. The results of this study indicate that the Halal Green Packaging variable has a significant effect on Green Purchase Intention (study: Ades bottled water in Jepara) with a significance value of 0.000. that the Halal Green perceived value variable has a significant effect on Green Purchase Intention (study: Ades bottled water in Jepara) with a significance value of 0.009. that the variables Halal Green Packaging, Green Halal Product, Halal Green Perceived Value simultaneously have a positive and significant effect on Green Purchase Intention (study: Ades bottled water in Jepara) with a significance value of 0.000.